2021
DOI: 10.1002/adfm.202010537
|View full text |Cite
|
Sign up to set email alerts
|

Physical Unclonable Anticounterfeiting Electrodes Enabled by Spontaneously Formed Plasmonic Core–Shell Nanoparticles for Traceable Electronics

Abstract: Counterfeit electronics are a growing problem for the electronic information industry worldwide, so developing unbreakable security tags is crucial to ensure the trustworthiness and traceability of electronics. Traditional anticounterfeiting and trace solutions rely on reproducible deterministic processes and additional labels, which can still be copied or faked by counterfeiters. Herein, physical unclonable functions enabled by spontaneously formed plasmonic core–shell nanoparticles on electrodes are proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…Fukuoka et al reported discrete self-assemblies of Au nanoparticles (AuNPs) and a reporter molecule; and demonstrated long-lived, on-dose authentication of commercial tablets 23 . In this manner, nanoparticles assembles are common in SERS PUFs 24 29 . Multiplex encoding is important for PUF taggants; SERS taggants have the advantage of enabling researchers to choose the reporter molecule from a diverse set of Raman-active molecules.…”
Section: Introductionmentioning
confidence: 97%
“…Fukuoka et al reported discrete self-assemblies of Au nanoparticles (AuNPs) and a reporter molecule; and demonstrated long-lived, on-dose authentication of commercial tablets 23 . In this manner, nanoparticles assembles are common in SERS PUFs 24 29 . Multiplex encoding is important for PUF taggants; SERS taggants have the advantage of enabling researchers to choose the reporter molecule from a diverse set of Raman-active molecules.…”
Section: Introductionmentioning
confidence: 97%
“…The design and development of novel encoded surfaces are of great research interest in today's world for use in anti-counterfeiting and authentication applications. Although the majority of encoded surface applications relate to the prevention of light, [20,21] carbon nanotubes, [22] spherical [23,24] and rod shaped [25] plasmonic nanoparticles, silver nanoislands, [26] core-shell nanoparticles, [27] polymeric particles, [28] diamonds, [29] and fluorescent compounds. [30] For the development of PUFs, fluorescent compounds are particularly interesting because they allow for rapid and simple authentication with multiple and interactive challenge-response pairs using facile and well-developed spectroscopic/microscopic techniques and portable tools.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Starting from the seminal work by Pappu et al., [ 6 ] optical PUF systems have been an active research area. [ 10–17 ] In the past decade, a range of material types and manufacturing routes have been studied to demonstrate PUFs using silica microparticles, [ 6 ] inherent randomness of surfaces, [ 18,19 ] randomly positioned scatterers challenged by quantum states of light, [ 20,21 ] carbon nanotubes, [ 22 ] spherical [ 23,24 ] and rod shaped [ 25 ] plasmonic nanoparticles, silver nanoislands, [ 26 ] core‐shell nanoparticles, [ 27 ] polymeric particles, [ 28 ] diamonds, [ 29 ] and fluorescent compounds. [ 30 ]…”
Section: Introductionmentioning
confidence: 99%
“…Physically unclonable functions (PUFs) exploit the inherently stochastic physical features at the microscopic level as one-way physical functions, which are easy to fabricate but practically impossible to replicate even by the original manufacturer. [16,17] PUFs possess a lot of attractive properties such as uniqueness, unclonability, unpredictability, tamper evidency, and so on, [18,19] making them the perfect candidates for unbreakable security hardwares. [20][21][22][23] Private keys of the PUFs are inherently hidden in the complex microscopic stochastic physical features, which can be generated only at the time of the right physical stimuli or challenges.…”
Section: Introductionmentioning
confidence: 99%